The Effect Of Increasing Price And Scarcity Of Fuel (BBM) On Fisherman's Income In New Ketapang Village Semidang Alas Maras District Seluma District - Desi Fitria; Ezi Surya Pratama; Nensi Yuniarti Zs; Dinal Eka Pertiwi; Hernadianto Hernadianto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to examine the effect of rising prices and scarcity of fuel oil (BBM) on fishermen's income in Ketapang Baru Village, Semidang Alas Maras District, Seluma Regency. The population in this study consisted of 60 fishermen, the research sample was 60 fishermen by taking the entire population. The type of research conducted in this research is descriptive quantitative research.The data used in this research is quantitative data. Where is the use of secondary data in the form of questionnaires that are distributed to fishermen. The data is processed using the SPSS application, namely software that functions to analyze data, perform statistical calculations both for statistics with basic windows.By using the f test analysis technique, the variables increasing the price of fuel oil (XI), scarcity of fuel oil (X2), simultaneously (simultaneously) affect fishermen's income (Y). This is shown by the results of the f' test that the significance value is 0.000. This significance value is less than 0.05. This means that there is a significant effect of rising fuel prices (XI) and fuel scarcity (X2) on fishermen's income (Y.